(3GdJQHjI GdLSejI ddCHfGA hGdBHGA (B/s - (3GdbGVj, SYjO ESeGYjds ((3GdbGgQI (B:s (3YGde GdcJH,s, 2013)
(3jJMOK gPG GdcJGH Yf GdJQHjI GdLSejI ddCHfGA hGdBHGA MjK Ef GdJQHjI GdESdGejI gj GdJfejI GdTGedI dLejY LhGfH TNUjI GdaQO (B((3LSejG hYbdjG hYbGFOjG hQhMjG hCNdGbjG hGLJeGYjG hfaSjG hEQGOjG hLfSjG hLeGdjG(B) (3hPdc aj VhA eG LGA Hg GdESdGe MJi jchf gPG GdaQO YGHOG ddg hMOg YHhOjI JMbb dg GdahR HGdOfjG hGdBNQI hJLYdg dHfI NjQI aj HfGA eLJeYg hESYGO GdHTQjI hYdi VhA Pdc jfGbT gPG GdcJGH GdJQHjI GdLSejI ddCHfGA hGdBHGA aj GdESdGe(B.s
(3HHdjhLQGajI (B: (3UaMI (B171-174.s
Keywords: (3GdJQHjI GdESdGejIs; (3GdESdGe hGdJQHjI GdHOfjIs; (3GdBHGA hGdCHfGAs -- (3LhGfH OjfjIs